From thrombasthenia to next generation thrombocytopenia: Neonatal alloimmune thrombocytopenia induced by maternal Glanzmann thrombasthenia. Issue 12 (14th September 2018) - Barg, Assaf Arie; Hauschner, Hagit; Luboshitz, Jacob; Livnat, Tami; Straus, Tzipi; Levy‐Mendelovich, Sarina; Lubetsky, Aharon; Rosenberg, Nurit; Kenet, Gili
Abstract: Background: Glanzmann thrombasthenia (GT) is a rare autosomal recessive disorder of platelet function caused by mutations in the genes coding for integrin αIIbβ3. The aim of this study was to examine the outcome of newborns of GT mothers, with emphasis on thrombocytopenia and bleeding manifestations and their relation to maternal antiplatelet antibodies. Procedure: Medical files of all female patients with GT treated in a single tertiary center from 1999 to 2017 were searched for details on pregnancy and birth. The medical files of their newborns were retrieved, and data on the postnatal course were collected. Results: Nine babies were born to five patients with GT at our center during the study period. Three of the nine newborns had severe thrombocytopenia, and all three were offspring of GT mothers who were positive for antiplatelet antibodies. Conclusion: Pregnant GT patients should be examined for platelet antibodies. Assessment and management protocols (including treatment with intravenous immunoglobulins) for fetal and neonatal alloimmune thrombocytopenia should be considered.